Safety and immunogenicity of Vi-typhoid conjugate vaccine co-administration with routine 9-month vaccination in Burkina Faso: A randomized controlled phase 2 trial. (July 2021) - Sirima, Sodiomon B.; Ouedraogo, Alphonse; Barry, Nouhoun; Siribie, Mohamadou; Tiono, Alfred; Nébié, Issa; Konaté, Amadou; Berges, Gloria Damoaliga; Diarra, Amidou; Ouedraogo, Moussa; Bougouma, Edith C.; Soulama, Issiaka; et al.
Highlights: This is the first study on the co-administration of typhoid conjugate vaccine (TCV) in West Africa. Co-administration of TCV with routine vaccines in a typhoid-endemic country was successful. TCV was safely co-administered at nine months with yellow fever and measles-rubella vaccines. Single-dose TCV was immunogenic in 9-month-old children. There was no safety signal related to TCV vaccination or co-administration. Abstract: Objectives: In 2017, the World Health Organisation (WHO) pre-qualified a single-dose typhoid conjugate vaccine (TCV) and identified TCV co-administration studies as a research priority. Accordingly, we tested co-administration of Typbar TCV® (Bharat Biotech International) with measles-rubella (MR) and yellow fever (YF) vaccines. Methods: We conducted a randomized, double-blind, and controlled, phase 2 trial in Ouagadougou, Burkina Faso. Healthy children aged 9–11 months were randomized 1:1 to receive TCV (Group 1) or control vaccine (inactivated polio vaccine (IPV), Group 2). Vaccines were administered intramuscularly with routine MR and YF vaccines. Safety was assessed by (1) local and systemic reactions on days 0, 3, and 7; (2) unsolicited adverse events within 28 days; and (3) serious adverse events (SAEs) within six months after immunization. Results: We enrolled, randomized, and vaccinated 100 eligible children (49 Group 1 and 51 Group 2). Safety outcomes occurred with similar frequency in both groups: local/solicited reactions (Group 1: 1/49, Group 2: 3/50), systemic/solicited reactions (Group 1: 4/49, Group 2: 9/50), unsolicited adverse events (Group 1: 26/49, Group 2: 33/51), and SAEs (Group 1: 2/49, Group 2: 3/51). TCV conferred robust immunogenicity without interference with MR or YF vaccines. Conclusion: TCV can be safely co-administered with MR and YF vaccines to children at the 9-month vaccination visit.